2022
DOI: 10.1001/jamasurg.2021.5561
|View full text |Cite|
|
Sign up to set email alerts
|

Paradoxical Association of Hyperglycemia and Surgical Complications Among Patients With and Without Diabetes

Abstract: IMPORTANCE Surgical complications associated with perioperative hyperglycemia are conventionally associated with diabetes, but, paradoxically, prior cohort studies have found that patients without diabetes have greater risk of complications at similar levels of hyperglycemia compared with patients with diabetes.OBJECTIVE To describe the association between perioperative hyperglycemia and surgical complications in a population of surgical patients without diabetes receiving routine blood glucose testing and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Yet hyperglycemia in patients without diabetes might be more harmful. For example, in a recent retrospective cohort study, patients without diabetes developed more postoperative complications than those with diabetes at similar levels of hyperglycemia ( 44 ). In another study of 3026 patients following minor stroke or transient ischemic accident, those without diabetes who developed stress hyperglycemia had a higher risk of stroke recurrence within 90 days ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet hyperglycemia in patients without diabetes might be more harmful. For example, in a recent retrospective cohort study, patients without diabetes developed more postoperative complications than those with diabetes at similar levels of hyperglycemia ( 44 ). In another study of 3026 patients following minor stroke or transient ischemic accident, those without diabetes who developed stress hyperglycemia had a higher risk of stroke recurrence within 90 days ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative hyperglycemia occurs in 15% to 75% of surgical patients, approximately one third of whom have no history of diabetes mellitus. [1][2][3][4][5][6] Transient hyperglycemia in patients without diabetes is referred to as stress hyperglycemia (SH). Stress hyperglycemia is thought to be mediated by cytokines and counter-regulatory hormones, including glucagon, cortisol, catecholamines, and growth hormone released in response to physiologic stresses, such as illness or surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive hyperglycemia, even for a short period, causes organ damage via reactive oxygen species, 1 increased susceptibility to infection, 2 and impaired blood reperfusion 3 . In the postoperative setting, hyperglycemia is associated with serious complications in diabetic and non‐diabetic patients 4 . A pivotal study on hyperglycemia intervention was conducted by G van den Berghe et al, demonstrating that tight glycemic control (controlling the glucose level between 80 and 110 mg/dL) significantly improved the mortality rate among patients admitted to the surgical intensive care unit (ICU) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…3 In the postoperative setting, hyperglycemia is associated with serious complications in diabetic and non-diabetic patients. 4 A pivotal study on hyperglycemia intervention was conducted by G van den Berghe et al, demonstrating that tight glycemic control (controlling the glucose level between 80 and 110 mg/dL) significantly improved the mortality rate among patients admitted to the surgical intensive care unit (ICU). 5 However, subsequent studies have reported contradictory results, [6][7][8] and a growing body of evidence has concluded that reducing glycemic variability and choking off severe hypoglycemia are more important factors in glycemic management than merely maintaining low glucose levels.…”
Section: Introductionmentioning
confidence: 99%